2012
DOI: 10.1096/fj.11-195941
|View full text |Cite
|
Sign up to set email alerts
|

A novel selective metabotropic glutamate receptor 4 agonist reveals new possibilities for developing subtype selective ligands with therapeutic potential

Abstract: Metabotropic glutamate (mGlu) receptors are promising targets to treat numerous brain disorders. So far, allosteric modulators are the only subtype selective ligands, but pure agonists still have strong therapeutic potential. Here, we aimed at investigating the possibility of developing subtype-selective agonists by extending the glutamate-like structure to hit a nonconsensus binding area. We report the properties of the first mGlu4-selective orthosteric agonist, derived from a virtual screening hit, LSP4-2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 47 publications
5
95
0
1
Order By: Relevance
“…5a to c, the three PAMs are located closely to the hydroxyl in Ser760 5.47 and Ser825 7.35 . So the hydrogen acceptor groups in the PAMs formed two hydrogen bonds with Ser760 5.47 and , respectively, indicating the importance of these two residues, which was consistent with former reports (18,26,64). Other residues also contributed to the binding and selectivity due to their hydrophobic nature, including (selective residues).…”
Section: Mglur4 Bound With Its Highly Selective Pamssupporting
confidence: 87%
See 1 more Smart Citation
“…5a to c, the three PAMs are located closely to the hydroxyl in Ser760 5.47 and Ser825 7.35 . So the hydrogen acceptor groups in the PAMs formed two hydrogen bonds with Ser760 5.47 and , respectively, indicating the importance of these two residues, which was consistent with former reports (18,26,64). Other residues also contributed to the binding and selectivity due to their hydrophobic nature, including (selective residues).…”
Section: Mglur4 Bound With Its Highly Selective Pamssupporting
confidence: 87%
“…This indicated that potential selectivity can be found in group III. Goudent et al (18) recently reported an orthosteric bitopic mGluR4 agonist with more than 30-fold selectivity over other group III mGluRs.…”
Section: Introductionmentioning
confidence: 99%
“…All types of mGlu 4 activators, agonists, ago-PAMs, and PAMs exhibiting high degree of cooperativity have been shown to be active in vivo (8,11,33,43,44,(48)(49)(50)(51). It can be speculated that pure mGlu 4 PAMs may be devoid of side effects but, to date, no clear adverse effect has been observed (8,50,51). Thus, for medicinal chemists to find the best therapeutic profile of mGlu 4 allosteric ligands, further experiments will be necessary to elucidate this point.…”
Section: Discussionmentioning
confidence: 99%
“…All 4 PAMs induced mobilization of intracellular calcium, suggesting that they all possess agonist activity, albeit very low for MPEP. The EC 50 values measured for VU0415374, VU0155041, PHCCC, and MPEP are 0.32 6 0.23 (n = 4), 11 6 2.9 (n = 4), 28 6 17 (n = 4), and 110 6 30 mM (n = 4), respectively. Agonist potencies, defined as 1/EC 50 , are in the same rank order as those given by the operational efficacies (t) provided by the operational model (Table 1).…”
Section: Analysis Of the Allosteric Agonist Activity Of Mglu 4 Pamsmentioning
confidence: 91%
“…While targeting this region has already been proposed as a strategy for the design of subtype-selective group III mGlu receptor agonists (Acher et al, 2011;Goudet et al, 2012), mGlu4, mGlu6, and mGlu8 receptors all contain functional chloride sites. In contrast to the claim that all mGlu receptors share the putative chloride binding site (Acher et al, 2011), our results demonstrate that this site is not conserved at mGlu2 receptors.…”
Section: Discussionmentioning
confidence: 99%